EMPOWERING THE ARTS: EXPLORING THE ROLE OF THEATRICAL ACTIVITIES IN PEACE BUILDING FOR HIGH-RISK CHILDREN - Pravina Manoharan; Mumtaz Begum Aboo Backer, (Jurnal Gendang Alam (GA), 2023)
This study delves into theatre's role in peacebuilding efforts targeting high-risk children, with a special focus on two projects in Penang, Malaysia. These projects sought to address several key inquiries: firstly, what is the significance of peacebuilding projects for high-risk children, secondly, what theatre activities are suitable for creating peacebuilding projects for high-risk children and thirdly, how can children empower the arts through theatre activities. "High-risk children" here refers to Rohingya refugee children, who are casualties of ethnic unrest in Myanmar, and children from Penang Shan Home, who face challenges like family issues and neglect. These children bring with them layers of untold stories, and the two different research projects posit theatre as a suitable intervention platform towards peacebuilding and a space for children empower the arts through their voices. This is an action-based research that employed a variety of methodologies, including theatre-based processes, interviews, observational techniques, and the collection of children’s reflections that culminated in two stage productions namely Jungle Book The Musical and Sang Kancil Speaks: Strange Times in Alam Rimba. The research yielded promising outcomes as the children in both projects put on a one hour production entirely in English, a medium of instruction many of them were uncomfortable with prior to the project. Reflections from the respective teachers and the children themselves revealed that there was positive change overall from the children’s behaviour, communication skills, their interaction with one another and with their teachers.